Relationship Between Knowledge and Attitude with Unsafe Action of Veneer Setting Workers at PT Abhirama Kresna : A Cross Sectional Study - Beti Setiyaningsih; Wartini Wartini (International Journal of Public Health, 2025)
Unsafe action is an action that does not comply with established procedures and rules which can cause work accidents. Unsafe action occurs for two reasons, such as unintentional errors and active errors or rule violations. Factor affecting unsafe action is internal and external factors. This research aims to examine the relationship between attitudes and knowledge towards unsafe action on section workers veneer setting at PT Abhirama Kresna. This research is a quantitative research using a cross sectional study design. The population in this study was 128 workers with 97 sample respondents. The variables in this study were knowledge, attitudes and unsafe actions. Bivariate analysis uses the chi square statistical test with a confidence level of 95%.  This research shows that knowledge does not have a significant relationship with unsafe action (p-value = 0.985; PR (CI 95%) = 0.288–3.391). On the other hand, attitude has a significant relationship with unsafe action (p-value = 0.022; PR (CI 95%) = 0.099–0.868).